Enhanced quantum efficiency of AlGaN photodetectors by patterned growth. Issue 5 (5th November 2014) - Knigge, A.; Brendel, M.; Zeimer, U.; Helbling, M.; Knauer, A.; Brunner, F.; Kueller, V.; Einfeldt, S.; Weyers, M.
<x xml:space="preserve">Abstract</x> Al0.45Ga0.55N metal–semiconductor–metal photodetectors were grown by MOVPE on planar and on stripe patterned epitaxial laterally overgrown (ELO) AlN/sapphire templates. By comparing devices on different template types, the influence of the average dislocation density, the distribution of dislocations, and composition modulations due to inhomogeneous gallium incorporation on the external quantum efficiency (EQE) were evaluated. The reduction of the average dislocation density from 6 × 109 cm−2 on the planar template to about 2 × 109 cm−2 by ELO increases the EQE. For electron transport perpendicular to the ELO stripes, this increase is about 70%. Due to the stripe‐like dislocation distribution in the absorber layers on ELO templates, the EQE becomes up to a factor of 3 higher than for planar templates, when the electrodes are perpendicular to the ELO stripes and electron transport is along the stripes. Photoconductive gain was found at elevated bias for absorber layers on standard ELO templates with electrodes perpendicular to the ELO stripes. The gain can be attributed to carrier transport in zig‐zag shaped Ga‐rich channels caused by facetted growth on ELO templates. The gain only appears, if the aluminum mole fraction differences Δx are higher than 0.07. At 30 V bias, the EQE of such detectors is more than 3 orders of magnitude higher compared to planar device.